2021
DOI: 10.3390/ijms22147315
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Diosmin in Pharmaceutical Products with Chemically Modified Voltammetric Sensors

Abstract: In this paper, the electrochemical behavior of two types of sensors based on modified screen-printed electrodes (one screen-printed electrode based on carbon (SPCE) and another screen-printed electrode modified with Prussian Blue (PB/SPCE)) was studied with the aim of sensitive detection of diosmin, an active pharmaceutical compound from the class of flavonoids. The scan electron microscopy technique was used for the morphological characterization of PB/SPCE. The preliminary analysis assessed the electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The cyclic voltammogram of the SPCE/HRP biosensor shows no peaks in the analyzed solution, while two pairs of redox peaks are observed for SPCE/PB/HRP. It is observed that the SPCE/PB/HRP biosensor is more sensitive than the other biosensor due to Prussian blue, which is electroactive, and the electrochemical processes taking place at the biosensor surface are shown in Equations ( 1) and ( 2) [44][45][46]. The cyclic voltammogram of the SPCE/HRP biosensor shows no peaks in the analyzed solution, while two pairs of redox peaks are observed for SPCE/PB/HRP.…”
Section: Characterization Of Biosensors By Cyclic Voltammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclic voltammogram of the SPCE/HRP biosensor shows no peaks in the analyzed solution, while two pairs of redox peaks are observed for SPCE/PB/HRP. It is observed that the SPCE/PB/HRP biosensor is more sensitive than the other biosensor due to Prussian blue, which is electroactive, and the electrochemical processes taking place at the biosensor surface are shown in Equations ( 1) and ( 2) [44][45][46]. The cyclic voltammogram of the SPCE/HRP biosensor shows no peaks in the analyzed solution, while two pairs of redox peaks are observed for SPCE/PB/HRP.…”
Section: Characterization Of Biosensors By Cyclic Voltammetrymentioning
confidence: 99%
“…)[44][45][46].Fe III [Fe II (CN) 6 ] + 4e − + 4K + ↔ K 2 Fe II [Fe II (CN) 6 ] Fe III [Fe II (CN) 6 ] − 3e − + 3Cl − ↔ Fe III [Fe III (CN) 6 •Cl] 3…”
unclassified
“…Alternative methods include electrochemical techniques that provide fast and accurate results [ 40 ]. Electrochemical sensors and biosensors have become increasingly diverse both structurally and in the functionalisation of the nanomaterials used as carriers to make determinations as sensitive, selective and easy as possible, using small amounts of samples without the need for complex pre-preparation [ 41 , 42 , 43 , 44 , 45 , 46 ]. The literature provides valuable information on sensitive and selective techniques, sensors and biosensors for the determination of oleuropein, tyrosol and hydroxytyrosol from real samples of VOO [ 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%